Leakage and spillover effects of forest management on carbon storage: theoretical insights from a simple model - Magnani, Federico; Dewar, Roderick C.; Borghetti, Marco (Tellus. Series B, Chemical and physical meteorology, 2009)
Leakage (spillover) refers to the unintended negative (positive) consequences of forest carbon (C) management in one area on C storage elsewhere. For example, the local C storage benefit of less intensive harvesting in one area may be offset, partly or completely, by intensified harvesting elsewhere in order to meet global timber demand. We present the results of a theoretical study aimed at identifying the key factors determining leakage and spillover, as a prerequisite for more realistic numerical studies.We use a simple model of C storage in managed forest ecosystems and their wood products to derive approximate analytical expressions for the leakage induced by decreasing the harvesting frequency of existing forest, and the spillover induced by establishing new plantations, assuming a fixed total wood production from local and remote (non-local) forests combined.We find that leakage and spillover depend crucially on the growth rates, wood product lifetimes and woody litter decomposition rates of local and remote forests. In particular, our results reveal critical thresholds for leakage and spillover, beyond which effects of forest management on remote C storage exceed local effects. Order of magnitude estimates of leakage indicate its potential importance at global scales.